Weak α-skew Armendariz ideals - Nikmehr, M.J.; Pazoki, M.; Tavallaee, H.A. (Український математичний журнал, 2012)
We introduce the concept of weak α-skew Armendariz ideals and investigate their properties. Moreover, we prove that I is a weak α-skew Armendariz ideal if and only if I[x] is a weak α-skew Armendariz ideal. As a consequence, we show that R is a weak α-skew Armendariz ring if and only if R[x] is a weak α-skew Armendariz ring. Введено поняття слабких α-косих iдеалiв Армендарiза та дослiджено їх властивостi. Крiм того, доведено, що I є слабким α-косим iдеалом Армендарiза тодi i тiльки тодi, коли I[x] є слабким α-косим iдеалом Армендарiза. Як наслiдок, показано, що R є слабким α-косим кiльцем Армендарiза тодi i тiльки тодi, коли R[x] є слабким α-косим кiльцем Армендарiза.